Pengaruh Tingkat Cekaman Salinitas Terhadap Pertumbuhan Beberapa Varietas Tanaman Padi (Oryza sativa L) - Hasibuan, Wahyu Ardica; Ginting, Jaya Sumana; Wardani, Dwika Karima (Universitas Medan Area, 2026)
Rice (Oryza sativa L.) is a major food commodity, but its production is often threatened by abiotic stresses, one of which is salinity (high salt content) in agricultural land, especially in tidal swamp land or due to seawater intrusion. Salinity can inhibit growth and reduce rice productivity through three main mechanisms: (1) osmotic stress that disrupts water and nutrient absorption, (2) toxicity of sodium (Na+) and chloride (Cl−) ions that disrupt metabolism, and (3) nutrient imbalance. The salinity tolerance limit for paddy rice that is compatible with high productivity is generally less than 3.74 dS/m. This study is entitled The Effect of Salinity Stress Levels on the Growth of Various Rice Varieties (Oryza sativa L). This study is a salinity treatment on various rice varieties at various levels. The purpose of this study is to determine the types of varieties that are tolerant to different levels of salinity. The study used a factorial randomized block design (RAK) with four varieties as treatment factors: Nutrizing variety (V1), Inpari variety (V2), Inpari33 variety (V3), and Mekonga variety (V4). The second factor was the level of salinity stress, consisting of: C1 = 0, C2 = 4, C3 = 8. The observation parameters measured were plant height (cm), number of tillers, number of leaves, and flowering age, with most results showing no significant differences.